Ensuring the Quality and Accessibility of Education in Times of War: Guidelines and Initiatives of the International Community - Liubomyra Iliichuk; Oksana Tsiuniak; Oleksii Vorobets (Vasyl Stefanyk Precarpathian National University, 2024)
The article is devoted to the problem of functioning of Ukrainian education during the period of martial law. The analysis of international organizations dealing with the problems of protection of education, ensuring its quality and accessibility in crisis situations is made. The emphasis is placed on the fact that the international community recognizes education as an inalienable human right which must be ensured under any circumstances, even in the context of military conflicts, and this determines the key trends in the activities of international organizations in the context of supporting Ukrainian education. It is noted that the violation of the right to education guaranteed by national legislation and international acts determines the need to find new innovative solutions for the development of education, a qualitative rethinking of the content and format of education, timely and effective response to the challenges of today associated with the transformation of relations and connections between the subjects of the educational process. The article analyzes domestic and international initiatives to protect Ukrainian education, ensure its quality and accessibility for all participants in the educational process, and organize education for internally displaced persons and Ukrainian refugees abroad. Some examples of international support for Ukrainian education, as well as for children and youth, educators and scientists in the framework of educational initiatives and projects are presented. It is emphasized that international support for the development of mechanisms to protect Ukrainian education, ensure its accessibility to all participants in the educational process, and create conditions for the quality provision of educational services under martial law is extremely valuable for the development of our country, which makes it necessary to study the experience and effective practices of international support for Ukrainian education during the russian-Ukrainian warn.